Pengaruh Label Bpom Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Konsumen Pada Produk Skincare Skintific (Studi Kasus Pada Mahasiswi FEB Angkatan 2019) - Anggraini Tri Ayuningtyas; Budi Wahono; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of the BPOM Label and Electronic Word Of Mouth on Consumer Purchase Decisions for Skincare Skintific Products in case studies of FEB class 2019 students. The type of research used is quantitative research by distributing questionnaires, using the Malhotra formula because the population of Skintific users is not known with certainty. the sample used non- probability sampling method with purposive sampling technique with a total sample of 75 respondents. In data processing using SPSS, to solve problems in analyzing validation tests, reliability tests, normality tests, classical assumption tests, hypothesis tests, multiple linear regression and adjusted R square tests. The results of the study are the effect of the BPOM label and electronic word of mouth partially or simultaneously having a positive and significant effect on purchasing decisions. Keywords: BPOM Label, Electronic Word Of Mouth, Purchasing Decision.